2022
DOI: 10.1136/archdischild-2021-323532
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in the management of neonatal early-onset sepsis?

Abstract: The expert guidelines highlighted in this review provide an evidence-based framework for approaching at-risk infants and allow for a more limited and standardised approach to antibiotic use. While these guidelines have significantly reduced antibiotic utilisation worldwide, optimally each unit would individualise their approach to early onset sepsis (EOS) based on the neonatal population they serve and available resources. As advancements in EOS research continue and limitations with sepsis prediction tools ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…The diagnosis of both EOS and LOS involves difficulty as sepsis in neonates usually manifests atypically [ 46 , 47 , 48 ]. Multiple common, non-infectious conditions have a similar clinical presentation to that of neonatal infection, while laboratory tests are of limited value due to their low sensitivity and the variability of normal limits in the neonatal period [ 49 ].…”
Section: Neonatal Sepsismentioning
confidence: 99%
“…The diagnosis of both EOS and LOS involves difficulty as sepsis in neonates usually manifests atypically [ 46 , 47 , 48 ]. Multiple common, non-infectious conditions have a similar clinical presentation to that of neonatal infection, while laboratory tests are of limited value due to their low sensitivity and the variability of normal limits in the neonatal period [ 49 ].…”
Section: Neonatal Sepsismentioning
confidence: 99%
“…Empirical antibiotics recommended for the management of NS by different guidelines include benzylpenicillin, ampicillin or amoxicillin, and aminoglycosides (mainly gentamicin) [ 15 , 16 , 17 ]. Pediatric survey data from 56 countries support that gentamicin and ampicillin are the most prescribed antibiotics in hospitalized neonates in Africa, the Americas, the Eastern Mediterranean, Europe, and South-East Asia, while in the Western Pacific region most common are amoxicillin in combination with β-lactamase inhibitor, ceftizoxime, and meropenem [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current guidelines contain three general approaches to identify newborns with an increased risk of EONS: a categorical risk factor assessment, a multivariate risk assessment (early-onset sepsis calculator) and a risk assessment primarily based on newborn clinical conditions [ 16 ]. A meta-analysis showed that the implementation of the neonatal sepsis calculator reduced the use of empirical antibiotic treatment, with a relative risk of 56% when compared to categorical approaches [ 17 ].…”
Section: Introductionmentioning
confidence: 99%